The role of social dimensions on the urban sustainability (Study on the form and social structure integration in the peri-urban areas in Sulaimanyiah city) - Rasul, Hoshyar Qadir; Muhammed, Othman Kareem (Sulaimani Journal for Engineering Sciences, 2017)
Urban development and urban expansion, usually followed by transformations of cities and their surroundings (rural, urban or both). Communities , which have been lived in environments different from those experienced today, became living in hybrid environment, where different urban environments blend. Addressed to the State that result from this development and expansion, emerging negative social effects, which took as a base in exploring a rule of design strategies in restructuring of these areas. It is necessary in thus rapid urbanization situations, which causes an increased fragmentation and heterogeneity around cities, to create urban forms most appropriate for residual growth of these peri-urban settlements on the one hand, and for overall growth of the city as a unified unit, on the other hand. The importance of the study emerged from solving the problem of (integration of urban form and social structure) that may occur during and after the change in peri- urban areas surrounding the southern part of Sulaimaniyah city, due to building a new city (2020) as planned. The paper is trying to explore an appropriate strategy and a mechanism for how this process (reshaping) will occurred, in order to achieve the urban sustainability. So the social dimensions which have a crucial influences on sustainable re-configuration of the city, took as a study hypothec, in order to avoid a state of (urban segregation). To reach this goal, the (Qualitative methods) based as methodology, depending on the introspective views and inductive approaches to draw the proposed frame work, which treated by the study as a (new context), requires the new strategy, for areas around the city described as fragmented, affecting the overall view of urban form, and social cohesion in each settlement as well. The study at last, achieved that the configuration will come from the human interaction with both dynamic (social environment), and fixed attributes (natural environment). Besides of that, the social dimensions have had the crucial influences on the urban form in one side, and on the sustainable re-configurations process in the peri-urban areas in the other side.
Keywords: Urban growth; Peri- urban areas; Urban form; Sustainable Urban form; Urban configuration